Selecting Initial Conditions for Trajectory-Based Nonadiabatic Simulations - Janoš, Jiří; Slavíček, Petr; Curchod, Basile F E (Accounts of chemical research, 2025)
ConspectusPhotochemical reactions have always been the source of a great deal of mystery. While classified as a type of chemical reaction, no doubts are allowed that the general tenets of ground-state chemistry do not directly apply to photochemical reactions. For a typical chemical reaction, understanding the critical points of the ground-state potential (free) energy surface and embedding them in a thermodynamics framework is often enough to infer reaction yields or characteristic time scales. A general working principle is that the energy profile along the minimum energy paths provides the key information to characterize the reaction. These well-developed concepts, unfortunately, rarely stretch to processes involving the formation of a nonstationary state for a molecular system after light absorption.Upon photoexcitation, a molecule is likely to undergo internal conversion processes, that is, changes of electronic states mediated by couplings between nuclear and electronic motion, precisely what the celebrated Born-Oppenheimer approximation neglects. These coupled electron-nuclear processes, coined nonadiabatic processes, allow for the molecule to decay from one electronic state to the other nonradiatively. Understanding the intricate nonadiabatic dynamics is pivotal to rationalizing and predicting the outcome of a molecular photoexcitation and providing insights for experiments conducted, for example, in advanced light sources such as free-electron lasers.Nowadays, most simulations in nonadiabatic molecular dynamics are based on approximations that invoke a near-classical depiction of the nuclei. This reliance is due to practical constraints, and the classical equations of motion for the nuclei must be supplemented by techniques such as surface hopping to account for nonadiabatic transitions between electronic states. A critical but often overlooked aspect of these simulations is the selection of initial conditions, specifically the choice of initial nuclear positions and momenta for the nonadiabatic dynamics, which can significantly influence how well the simulations mimic real quantum systems across various experimental scenarios. The conventional approach for generating initial conditions for nonadiabatic dynamics typically maps the initial state onto a nuclear phase space using a Wigner quasiprobability function within a harmonic approximation, followed by a second approximation where the molecule undergoes a sudden excitation.In this Account, we aim to warn the experienced or potential user of nonadiabatic molecular dynamics about the possible limitations of this strategy for initial-condition generation and its inability to accurately describe the photoexcitation of a molecule. More specifically, we argue that the initial phase-space distribution can be more accurately represented through molecular dynamics simulations by using a quantum thermostat. This method offers a robust framework that can be applied to large, flexible, or even solvated molecular systems. Furthermore, the reliability of this strategy can be benchmarked against more rigorous approaches such as path integral molecular dynamics. Additionally, the commonly used sudden approximation, which assumes a vertical and sudden excitation of a molecule, rarely reflects the excitation triggered by laser pulses used in actual photochemical and spectroscopic experiments. We discuss here a more general approach that can generate initial conditions for any type of laser pulse. We also discuss strategies to tackle excitation triggered by a continuous-wave laser.